2017
DOI: 10.1177/2192568217699192
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Risk Factors of Reoperation Following Minimally Invasive Decompression for Lumbar Canal Stenosis Associated With Degenerative Scoliosis and Spondylolisthesis

Abstract: Study Design:Prospective cohort study.Objective:Microsurgical bilateral decompression via a unilateral approach (MBDU), a minimally invasive surgical (MIS) decompression method, has been performed for numerous degenerative lumbar diseases, including degenerative lumbar scoliosis (DLS) or degenerative spondylolisthesis (DS), at our institution. In this study, we evaluated the appropriateness of MBDU for DLS or DS patients.Methods:A total of 207 patients treated by MBDU were included (88 women and 119 men; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
(34 reference statements)
0
23
1
2
Order By: Relevance
“…Our univariate analysis was not able to identify any preoperative factors to predict poor outcome or reoperation. Previous studies, however, postulated that preoperative scoliotic disc wedging (Cobb angle ≥ 3°) and lateral listhesis 37,38 are associated with reoperation, while spur formation on the concave side of scoliotic curves may be a protective factor in curve progression. 35 Blumenthal et al reported that in patients with degenerative grade I lumbar spondylolisthesis who underwent conventional laminectomy, a facet angle > 50° was associated with a 39% rate of reoperation, and a disc height > 6.5 mm was associated with a 45% rate of reoperation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our univariate analysis was not able to identify any preoperative factors to predict poor outcome or reoperation. Previous studies, however, postulated that preoperative scoliotic disc wedging (Cobb angle ≥ 3°) and lateral listhesis 37,38 are associated with reoperation, while spur formation on the concave side of scoliotic curves may be a protective factor in curve progression. 35 Blumenthal et al reported that in patients with degenerative grade I lumbar spondylolisthesis who underwent conventional laminectomy, a facet angle > 50° was associated with a 39% rate of reoperation, and a disc height > 6.5 mm was associated with a 45% rate of reoperation.…”
Section: Discussionmentioning
confidence: 96%
“…38 The authors reported significant improvements in ODI scores in patients with deformity with no significant progression of scoliosis; however, there was a 25% reoperation rate, with 50% of these failures in patients with concurrent lateral listhesis. Conversely, a recent 2017 prospective study with 2-year follow-up compared outcomes in 207 patients with spinal stenosis with or without coexisting scoliosis (mean Cobb angle 14°) following tubular MIS-ULBD 37 and found significant increases in functional outcomes in all patients with an 8% reoperation rate, which was associated with preoperative scoliotic disc wedging (Cobb angle ≥ 3°) and lateral listhesis. Our tubular MIS-ULBD cohort was found to have a reoperation rate of 11%, which is consistent with rates reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2017), билатеральная интерламинарная декомпрессия с применением унилатерального доступа эффективна как при изолированном дегенеративном СПК, так и при СПК в сочетании со спондилолистезом и сколиозом. Авторы отмечают, что при сочетании дегенеративного СПК со сколиозом факторами риска неэффективности операции выступают латеральный спондилолистез и сколиотический угол >3° в сегменте L 4 -L 5 [35].…”
Section: Russian Journal Of Neurosurgeryunclassified
“…The key to this technique is to preserve the posterior elements of spine, for instance, intervertebral joints, intraspinal ligaments, supraspinatus ligaments, and paraspinal muscles, and may facilitate the preservation of stable spinal ligaments and the bone structures. [ 12 16 ] Because the preservation of the posterior component can minimize the damage to instability or scoliosis after the decompression, indications are extended to the lumbar diseases, involving DS or DLSS. Nevertheless, there is no consensus on these indications.…”
Section: Introductionmentioning
confidence: 99%